Improvement in properties of expansive clay by stabilizing with Buton Rock Asphalt - Rusbintardjo, Gatot (Penerbit UTM Press, 2015)
Subgrade is a soil layer underneath a constructed road pavement, airport runway or railway track. It is essential to make the layer stable and has sufficient shearing strength to withstand the traffic induced stresses without excessive deformation. If the subgrade soil is weak, it may need to be stabilized to improve its properties. This paper investigates the suitability of Buton Rock Asphalt (BRA) and natural sand in stabilizing expansive clay in order to be used as subgrade soil. Amount of 2%, 4%, 6%, and 8% of BRA by weight of soil were added while 5 to 25% of natural sand in increments of 5% by weight of soil was added to compare the effects of using natural sand and BRA in stabilizing expansive clay. Tests such as Atteberg Limit, California Bearing Ratio, and direct shear were conducted on both natural clay soil and clay stabilized BRA. From the study, it was found that BRA can improve bearing capacity of expansive clay soil better than the natural sand.